Regulation of Circular RNA CircNFATC3 in Cancer Cells Alters Proliferation, Migration, and Oxidative Phosphorylation - Karedath, Thasni; Al-Dasim, Fatima M.; Ahmed, Ikhlak; Al-Qurashi, Albandary; Raza, Afsheen; Andrews, Simeon Scott; Ahmed, Ayeda Abdulsalam; Ali Mohamoud, Yasmin; Dermime, Said; Malek, Joel A. (Frontiers in Cell and Developmental Biology, 2021)
Circular RNAs were once considered artifacts of transcriptome sequencing but have recently been identified as functionally relevant in multiple cancers. Although there is still no clear main function of circRNAs, several studies have revealed that circRNAs are expressed in a variety of eukaryotic organisms, demonstrate conservation across species, and are expressed in a regulated manner often independent of their parental linear isoforms. circNFATC3, an abundant and uncharacterized circular RNA of exon 2 and 3 from NFATC3, was identified in transcriptomic data of solid tumors. Here we show that circNFATC3 gain- and loss-of-function experiments using RNAi-mediated circRNA silencing and circular mini vector-mediated overexpression of circularized constructs in breast and ovarian cancer cell lines affect molecular phenotypes. The knockdown of circNFATC3 induces a reduction in cell proliferation, invasion, migration, and oxidative phosphorylation. Gain-of-function of circNFATC3 in MDA-MB-231 and SK-OV-3 cells show a significant increase in cell proliferation, migration, and respiration. The above results suggest that circNFATC3 is a functionally relevant circular RNA in breast and ovarian cancer.